Severe anemia in late pregnancy: a retrospective study at a tertiary care rural medical college in Gujarat, India - Sapre, Shilpa A.; Raithatha, Nitin S.; Bhattacharjee, Rumi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia in pregnancy is the commonest medical disorder in developing countries like India. It has multifactorial etiology and is associated with increased maternal and perinatal morbidity and mortality. The study aimed at analyzing the socio-demographic variables and also the maternal and perinatal outcome of pregnant women admitted to labour room with severe anaemia (Hb <7 gm%) late in pregnancy. Methods: This is a retrospective observational study done at a tertiary care rural medical college in Gujarat over a 3 year period from January 2014 to December 2016. Results: Results of the study were analyzed. Out of 3963 deliveries during the study period 225 (5.6%) patients were severely anaemic. There were 177 (78.6%) unbooked patients and 169 (75.1%) were multigravidas. Majority of patients belonged to under 24 yr age group. Maternal complications were in form of preterm labour (44%), pre-eclampsia-ecclampsia (24.8%), cardiac failure (2.2%), PPH (2.2%) maternal death (0.4%). Neonatal outcome was analyzed in terms of prematurity (44%), LBW (24.8%), NICU admission (15.1%), still birth (4.4%), neonatal death (11.5%). Conclusions: Severe anaemia during pregnancy is associated with adverse maternal and perinatal outcome. It is also one of the preventable indirect cause of maternal mortality. Imparting health education to adolescent girls, regular antenatal check-ups, early diagnosis and treatment along with active participation of ASHA workers at grass-root level might help in bringing down the prevalence. A more focused approach is warranted towards pregnant women in rural and underdeveloped areas of India.